2020
DOI: 10.1186/s12935-020-01435-0
|View full text |Cite
|
Sign up to set email alerts
|

RACK1 promotes miR-302b/c/d-3p expression and inhibits CCNO expression to induce cell apoptosis in cervical squamous cell carcinoma

Abstract: Background: Cervical squamous cell carcinoma (CSCC) is one of the main causes of cancer-related deaths in women worldwide. The present study was conducted with the main objective of determining the potential role of receptor for activated protein kinase C1 (RACK1) in CSCC through regulation of microRNA (miR)-302b/c/d-3p and Cyclin O (CCNO). Methods: The expression of RACK1, miR-302b/c/d-3p and CCNO in CSCC tissues and cells was measured by RT-qPCR and Western blot analysis. The interaction among RACK1, miR-302… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“… 19–23 We similarly explore the function of MAGI1‐IT1 as a ceRNA and determined that it was predicted to bind to miR-302d-3p, which is a miRNA that has previously been shown to suppress cervical squamous cell carcinoma tumor growth. 13 We confirmed the ability of MAGI1‐IT1 to sequester miR-302d-3p through both luciferase reporter and RIP assays, and we observed negative correlations between these two RNAs in GC patient tumor tissues. Importantly, miR-302d-3p inhibition was sufficient to reverse the impacts of MAGI1‐IT1 knockdown on GC cell proliferation, confirming that MAGI1‐IT1 regulates GC cell malignancy at least in part by serving as a ceRNA for miR-302d-3p.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“… 19–23 We similarly explore the function of MAGI1‐IT1 as a ceRNA and determined that it was predicted to bind to miR-302d-3p, which is a miRNA that has previously been shown to suppress cervical squamous cell carcinoma tumor growth. 13 We confirmed the ability of MAGI1‐IT1 to sequester miR-302d-3p through both luciferase reporter and RIP assays, and we observed negative correlations between these two RNAs in GC patient tumor tissues. Importantly, miR-302d-3p inhibition was sufficient to reverse the impacts of MAGI1‐IT1 knockdown on GC cell proliferation, confirming that MAGI1‐IT1 regulates GC cell malignancy at least in part by serving as a ceRNA for miR-302d-3p.…”
Section: Discussionsupporting
confidence: 74%
“…[19][20][21][22][23] We similarly explore the function of MAGI1-IT1 as a ceRNA and determined that it was predicted to bind to miR-302d-3p, which is a miRNA that has previously been shown to suppress cervical squamous cell carcinoma tumor growth. 13 We confirmed the ability of MAGI1-IT1 to sequester miR- Importantly, miR-302d-3p inhibition was sufficient to reverse the impacts of MAGI1-IT1 knockdown on GC cell proliferation, confirming that MAGI1-IT1 regulates…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Ribosomal receptor for activated C-kinase 1 (RACK1) is associated with chemoresistance and tumour growth [ 132 ], with increased levels of RACK1 correlating with tumour progression and fatality [ 133 ]. RACK1 may act via a variety of processes in tumours, including upregulating the assembly and activity of the NLRP3 inflammasome [ 132 , 134 ], miRNAs patterning [ 135 ], and AhR regulation [ 136 ]. Being a ribosomal protein, RACK1 modulates how ribosomes spatiotemporally coordinate patterned gene expression, including local translation process [ 137 ] and centrosome regulation [ 138 , 139 ].…”
Section: Wider Regulators Of the Tumour Microenvironment And Immunmentioning
confidence: 99%
“…Bioinformatics analysis of our study manifested that miR-302d-3p may directly target ITGB4. miR-302d-3p is a member of the miR-302 cluster that was initially found in human embryonic stem cells, which plays a crucial role in endometrial carcinoma (Li et al, 2018), cervical squamous cell cancer (Wang and Chen, 2020), and breast cancer (Sun et al, 2020a). More importantly, Wang et al (2019) have indicated that miR-302d-3p is expressed at higher levels in OA and may hinder the progression of OA via mediating cell viability in chondrocytes.…”
Section: Introductionmentioning
confidence: 99%